2018
DOI: 10.1021/acs.macromol.8b02156
|View full text |Cite
|
Sign up to set email alerts
|

Bisurea-Functionalized RAFT Agent: A Straightforward and Versatile Tool toward the Preparation of Supramolecular Cylindrical Nanostructures in Water

Abstract: Bis-ureahydrophilic polymer sticker RAFT polymerizationTTC unit Hydrogen bonding unit , , , … µm ABSTRACTWe report a versatile and simple approach to produce cylindrical micelles by the direct dissolution of polymers in water. The developed strategy relies on a RAFT agent functionalized by a bisurea sticker that allowed to synthesize a series of α-bisurea functionalized poly(N,Ndimethylacrylamide) (PDMAc), poly(acrylic acid) (PAA), polyacrylamide (PAM) and poly(2-(N,N-dimethylamino)ethyl acrylate) (PDMAEA) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 58 publications
1
22
0
2
Order By: Relevance
“…Cryo-TEM analyses showed that they assembled into cylindrical and/or spherical micelles (Figure 2 and Figure S2), as described before for PDMAc-U2 and PAA-U2. 12 Our data show that a lower DPn favored the formation of cylindrical over spherical micelles (see Table 1). For † Except PHEA2, which was not soluble.…”
Section: Self-assembly Of the Bisurea-functionalized Polymers In Watermentioning
confidence: 54%
See 2 more Smart Citations
“…Cryo-TEM analyses showed that they assembled into cylindrical and/or spherical micelles (Figure 2 and Figure S2), as described before for PDMAc-U2 and PAA-U2. 12 Our data show that a lower DPn favored the formation of cylindrical over spherical micelles (see Table 1). For † Except PHEA2, which was not soluble.…”
Section: Self-assembly Of the Bisurea-functionalized Polymers In Watermentioning
confidence: 54%
“…A series of bisurea-functionalized hydrophilic polymers (Scheme 1), namely poly(N,Ndimethylacrylamide) (PDMAc), poly(acrylic acid) (PAA), polyacrylamide (PAM), poly(N-4acryloylmorpholine) (PNAM) and poly(2-hydroxyethylacrylate) (PHEA), were synthesized using the recently reported bisurea-functionalized RAFT agent TTC-U2. 12,15 The polymerizations were performed in DMF, at 70 °C, using AIBN as an initiator and targeting a number-average degree of polymerization (DPn) ranging from 10 to 50. Generally, 70% monomer conversion was reached in less than 5 h (see Table S1), and after precipitation the polymers were analyzed by SEC and 1 H NMR.…”
Section: Synthesis Of Bisurea-functionalized Hydrophilic Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophilic polymers decorated with a bisurea sticker are known to form long rod-like assemblies in water 16 18 . Interestingly, Sijbesma et al showed that the length of the alkylene spacer connecting two urea groups plays an essential role: if two bisurea stickers differing by the size of the alkylene spacer are mixed, they form self-sorted assemblies, so that urea–urea hydrogen bonds are maximized 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Während die letztgenannten Beispiele auf supramolekularen Interaktionen zwischen Monomereinheiten der Polymerketten im Kern basierten, haben Rieger, Stoffelbach und Mitarbeiter erst kürzlich eine Bausatz‐Strategie entwickelt, die auf Interaktionen zwischen einzelnen Hafteinheiten am ω‐Ende jeder Polymerkette basiert. Sie entwarfen nämlich ein MacroRAFT‐Agens, das durch eine wasserstoffbrückengebundene Bis‐Harnstoff‐Hafteinheit funktionalisiert wurde, um den PISA‐Prozess über eine eindimensionale, gerichtete Selbstorganisation der Hafteinheiten in Richtung Nanofasermorphologie zu treiben, die durch die Bildung hydrophober Domänen während des PISA‐Prozesses noch verfestigt wird (Abbildung ). Dieses Konzept wurde erfolgreich bei der Synthese von Poly( N , N ‐dimethylacrylamid)‐ b ‐poly(2‐methoxyethylacrylat)‐Diblockcopolymeren getestet, die durch Dispersionspolymerisation in Wasser hergestellt wurden.…”
Section: Steuerung Der Partikelmorphologieunclassified